Heparin in the Treatment of Cerebral Malaria - M. Munir; H. Tjandra; T.H. Rampengan; I. Mustadjab; F.H. Wulur (Paediatrica Indonesiana, 1980)
Cerebral episodes in malaria are considered to be due to thrombin in the cerebral capillaries. Heparin is beneficial in arterial thrombosis, not only on account of its anticoagulating property, but also by virtue of its slight vasodilating effect which promotes collateral circulation. Based on these, a study was undertaken with the objective of finding out the effect of heparin in the treatment of cerebral malaria. Thirty-three cases admitted to the Child Health Department, Medical School, Sam Ratulangi University/Gunung Wenang Hospital, Manado from July /, 1973 until October 31, 1977 were divided into 2 groups: a study group receiving 300 u/kg bw/day of heparin either intramuscularly or intravenously for 3 consecutive days along with antimalarial drugs; and a control group receiving only antimalarial drugs. Thirteen out of 17 patients of the control group succumbed (76.5%) as compared to 2 out of 16 patients of the heparin group (12.5o/o). This study shows that heparin seems to be of real benefit in the treatment of cerebral malaria in children, since not only the mortality rate reduced significantly but the general condition improved rapidly.